Red light-triggered photoreduction on a nucleic acid template - Dutta, Subrata; Rühle, Jennifer; Schikora, Margot; Deussner-Helfmann, Nina S.; Heilemann, Mike; Zatsepin, Timofei; Duchstein, Patrick; Zahn, Dirk; Knoer, Guenther; Mokhir, Andriy (Chemical Communications, 2020)
Conjugate Sn(iv)(pyropheophorbide a)dichloride-(peptide nucleic acid) catalyzes reduction of azobenzene derivatives in the presence of complementary nucleic acid (NA) upon irridiation with red light (660 nm). This is the first red light-induced NA-templated photoreduction. It is highly sensitive to single mismatches in the NA-template and can detect down to 5 nM NAs.
CRIS-Team Scopus Importer:2020-09-11